Analysis of the implementation of Public Health Center Level Planning (PTP) in Pematang Raya Community Health Center, Simalungun Regency - Khairiyah Dwie Vanesa; Amira Arni; Muhammad Yunus Nasution (PT WIM Solusi Prima, 2026)
Community Health Center Planning (Perencanaan Tingkat Puskesmas/PTP) is an essential management function in the implementation of health services at community health centers. PTP plays a significant role in determining health priorities, developing health programs, and allocating resources to achieve healthcare service targets. Effective implementation of PTP is expected to improve the efficiency and effectiveness of health programs within the health center's working area. This study aimed to analyze the implementation of Community Health Center Planning (PTP) at Pematang Raya Community Health Center, Raya District, Simalungun Regency, North Sumatra. This study employed a qualitative descriptive method with a case study approach. The research was conducted at Pematang Raya Community Health Center from July to August 2026. Eight informants were selected using purposive sampling, consisting of the Head of the Community Health Center, Administrative Head, program coordinators, program managers, and health cadres. Data were collected through in-depth interviews, observation, and document review. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. Data validity was ensured through source and method triangulation. The findings revealed that the implementation of Community Health Center Planning at Pematang Raya Community Health Center had been conducted through several stages, including preparation, situation analysis, problem formulation, preparation of the Activity Proposal Plan (RUK), and preparation of the Activity Implementation Plan (RPK). The preparation stage involved establishing a planning team and assigning responsibilities to program managers. Situation analysis was conducted using program achievement data, health profiles, disease statistics, maternal and child health data, nutrition data, and the Healthy Indonesia Program with Family Approach (PIS-PK) data. Problem formulation was carried out through identification and prioritization of health problems based on community needs and program targets. The preparation of RUK and RPK was conducted participatively involving all program managers. Furthermore, cross-sectoral support from district and village governments, health cadres, and community leaders contributed to the planning and implementation of health programs. In conclusion, the implementation of Community Health Center Planning (PTP) at Pematang Raya Community Health Center has been carried out effectively and in accordance with the principles of community health center management. However, strengthening data analysis and cross-sectoral coordination remains necessary to further improve the effectiveness of health program planning.